Translating education neuroscience for teachers. (3rd July 2019) - Tham, Rachel; Walker, Zachary; Tan, Shi Hui Desiree; Low, Li Tong; Annabel Chen, Shen-Hsing
ABSTRACT: Translating Neuroscience to education involves providing accurate and simplified information about neuroscience to teachers. The aim of this research was to understand if providing translated abstracts from neuroscientific articles helped teachers understand content more thoroughly. Surveys, experimental manipulation, and focus group discussions were conducted with thirty teachers from two primary schools in Singapore. Teachers shared their familiarity with neuroscience, self-rated their understanding of neuroscientific abstracts, and provided feedback on the abstracts' translations. Results indicate that translated abstracts did not improve attitudes significantly; however, focus group discussions revealed that teachers were more interested in the applications of neuroscience research in classroom pedagogy. These findings highlight the importance of improving communication between neuroscientists and educators. Abbreviations: TENC: Translational Education Neuroscience Clearinghouse; AEDs: Allied Educators